In Candida albicans, phosphorylation of Exo84 by Cdk1-Hgc1 is necessary for efficient hyphal extension - Caballero-Lima, David (The American Society for Cell Biology, 2014)
The exocyst, a conserved multiprotein complex, tethers secretory vesicles before fusion with the plasma membrane; thus it is essential for cell surface expansion. In both Saccharomyces cerevisiae and mammalian cells, cell surface expansion is halted during mitosis. In S. cerevisiae, phosphorylation of the exocyst component Exo84 by Cdk1-Clb2 during mitosis causes the exocyst to disassemble. Here we show that the hyphae of the human fungal pathogen Candida albicans continue to extend throughout the whole of mitosis. We show that CaExo84 is phosphorylated by Cdk1, which is necessary for efficient hyphal extension. This action of Cdk1 depends on the hyphal-specific cyclin Hgc1, the homologue of G1 cyclins in budding yeast. Phosphorylation of CaExo84 does not alter its localization but does alter its affinity for phosphatidylserine, allowing it to recycle at the plasma membrane. The different action of Cdk1 on CaExo84 and ScExo84 is consistent with the different locations of the Cdk1 target sites in the two proteins. Thus this conserved component of polarized growth has evolved so that its phosphoregulation mediates the dramatically different patterns of growth shown by these two organisms.